Resistência à fratura de dentes com rizogênese incompleta simulada após o uso de medicações intracanais utilizadas na revitalização pulpar - Lima Neto, José Cordeiro (2018)
The objective of this study was to evaluate the short-term effect on fracture resistance of simulated immature teeth after the use of intracanal medications indicated in pulp revitalization. Materials and Methods: 180 bovine teeth were selected, sectioned coronally and apically and internally fragilized. The canals were irrigated with 20 ml of sodium hypochlorite. Intracanal medication was applied as follows: triple antibiotic paste (TAP) group (n=60) and calcium hydroxide (CH) group (n=60). No medication was used in the control group. Fracture resistance tests were performed after 7, 14 and 21 days. At each time interval, 20 teeth from each group had fractured in a universal test machine in a 1mm/min compression test. ANOVA, Tukey, Kruskall-Wallis and Mann-Whitney tests were performed to verify the effect of the type of medication on fracture resistance at each time point. Pearson and Spearman tests were also performed to verify the correlation between time and fracture resistance. The level of significance adopted was 5%. Results: In the first week, there were no differences between the groups (p = 0.322). In the second and third week, there was a statistical difference between the TAP group and the control group (p = 0.018 and 0.033, respectively). No statistical differences were found between CH and control group (p>0.05). In the intragroup analysis, it was verified that the fracture resistance in the TAP and CH group was reduced in the third week, with a statistical difference in relation to the first week (p≤ 0.05). The control group did not present statistical difference at different time intervals (p > 0.05). There was a negative correlation between time and fracture resistance for TAP (p=0.003) and CH group (p<0.001). Conclusion: The time that TAP and CH remained in the canal influenced the fracture resistance of bovine teeth with simulated incomplete root formation, and the reduction was significant from the second week for TAP group